The sweet spot : how Australia made its own luck - and could now throw it all away - Hartcher, Peter (Black Inc., 2014)
New updated editionThis book will change the way you think about your country ... Australians now officially have the best living conditions in the world. Our country is both fair and free - and the only developed nation to have avoided a recession in the past twenty years. So how did it happen and why don't we care?In The Sweet Spot Peter Hartcher takes readers on a vastly entertaining and thought-provoking tour through Australian politics and history. He shows how a convict colony could have become a banana republic but didn't, how Australia came through the global financial crisis - it wasn't j.